Effect of drinking water salinity on productive performance and blood biochemical parameters in Surti kids under tropical conditions - HARINI, K R; RANJEET SINGH, RANA; KUMAR, AMIT; SRIRANGA, K R (The Indian Journal of Animal Sciences, 2022)
The present study was carried out at Livestock Research Station, Navsari Agricultural University, Navsari, Gujarat to evaluate the effect of drinking water salinity on production and blood biochemical parameters. Apparently healthy 18 Surti kids were selected based on their body weight and subsequently were divided into three groups depending on different types of drinking water provided to them on free choice basis: T0 (animals receiving potable water available at LRS, NAU, Navsari having TDS about 1500-1600 ppm), T1 (Animals receiving drinking water having TDS about 4000 ppm.), T2 (Animals receiving drinking water having TDS about 6000 ppm). The salinity of drinking water significantly affected the dry matter intake and water intake in Surti kids without negatively affecting the bodyweight gain. Blood biochemical parameters such as glucose, total protein, creatinine, urea, and triglycerides were not affected by salinity of water. However, serum albumin and cholesterol had shown significantly higher concentration in the T2 group. From the findings of our investigation, it could be inferred that the provision of water having TDS up to 6000 ppm to the Surti kids doesn’t elicit any adverse effect on their performance up to 105 days.